A Novel Method for Solving Nonlinear Volterra Integro-Differential Equation Systems - Mohammad Hossein Daliri Birjandi; Jafar Saberi-Nadjafi; Asghar Ghorbani (Abstract and Applied Analysis)
An efficient iteration method is introduced and used for solving a type of system of nonlinear Volterra integro-differential equations. The scheme is based on a combination of the spectral collocation technique and the parametric iteration method. This method is easy to implement and requires no tedious computational work. Some numerical examples are presented to show the validity and efficiency of the proposed method in comparison with the corresponding exact solutions.